The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1970
DOI: 10.33736/bjrst.235.2014
|View full text |Cite
|
Sign up to set email alerts
|

Overall Diversity of Fruit-Feeding Butterflies (Lepidoptera: Nymphalidae) Along Vertical Gradient in a Peat Swamp Forest, Kota Samarahan, Sarawak

Abstract: A study which aims to investigate the vertical distribution pattern of nymphalids had been conducted in a peatswamp forest of Kota Samarahan, Sarawak. This 60-day sampling period which utilised baited traps as the mainsampling method, had resulted to 104 individuals from both ground and canopy levels. The lower stratumrevealed a higher diversity index (H’= 1.17466) in comparison with the canopy stratum. Nymphalinae representsthe most diverse subfamily at both levels, dominating almost half of the total individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This ecology is common for satyrines in general (e.g. Schulze et al, 2001;Gintoron and Abang, 2014), but most Coenonymphina are unusual in the subfamily as they occur in more or less open habitat.…”
Section: Ecology Of Argyronymphamentioning
confidence: 96%
See 2 more Smart Citations
“…This ecology is common for satyrines in general (e.g. Schulze et al, 2001;Gintoron and Abang, 2014), but most Coenonymphina are unusual in the subfamily as they occur in more or less open habitat.…”
Section: Ecology Of Argyronymphamentioning
confidence: 96%
“…fuscus , M . patiana ; Gintoron and Abang, 2014). Freshwater swamp forest in Indonesian Borneo ( M. anapita ; Husson et al., 2018).…”
Section: Ecology Of Coenonymphina and Relativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Houlihan et al (2013) reported that at least 11 species of butterfly in the peat swamp forest in Central Kalimantan were successfully identified. A total of 24 species were found in a peat swamp in Kota Samarahan, Sarawak, Malaysia (Gintoron and Abang 2014). Our previous study revealed that in the peat forest of Kotawaringin, Central Kalimantan, a total of 28 species of butterfly was found (Harmonis and Saud 2017).…”
Section: The Diversity Of Butterfly Speciesmentioning
confidence: 96%